РОЗРАХУНОК ПЕРЕТВОРЮВАЧА КУКА ЗА ДОПОМОГОЮ МЕТОДА УСЕРЕДНЕННЯ НА ОСНОВІ ТЕОРЕМ ЛАГРАНЖА - Руденко, Ю.В. (Інститут електродинаміки Національної академії наук України, 2022)
A mathematical model of the Cuk converter has been developed using the state-space averaging method based on Lagrange theorems for the mode of continuous currents and voltages at storage reactive elements. Analytical expressions are obtained based on relative variables, making it possible to calculate processes in the converter in a wide range of parameters at the control zone of the duration of switching intervals. The limiting dependences of converter parameters between the modes of discontinuous and continuous currents and voltages in storage elements are calculated to determine the effective modes of operation of the device. Analytical dependencies are obtained, making it possible to determine the maximum values ​​of currents and voltages in the elements of the converter over the entire switching range and allowing choosing these elements of the device with acceptable parameters at the stage of its design. Ref. 14, fig 5, table.